Analisis Pengaruh Tingkat Pendidikan, Upah Minimum Kabupaten dan Jumlah Penduduk terhadap Penyerapan Tenaga Kerja di Kabupaten Mojokerto - Rena Rigin Putri; Niniek Imaningsih (Al-Buhuts, 2023)
Labor is one of the important success factors in the process of economic development where the absorption of labor encourages regional development as a whole. The purpose of this study is to determine the effect of Education Level, District Minimum Wage, and Number of Population on Employment in Mojokerto Regency in 2007-2022 obtained from BPS Mojokerto Regency. The method used in this study is multiple linear regression analysis. The results of this study concluded that the level of education, district minimum wage and population simultaneously have an influence on employment in Mojokerto Regency. Partially, the level of education and population do not affect the absorption of labor in Mojokerto Regency, while the district minimum wage has an influence on the absorption of labor in Mojokerto Regency.